العوامل الاجتماعية لتدني مستوى التحصيل الدراسي دراسة ميدانية على تلاميذ الحلقة الأولى من مرحلة التعليم الأساسي في مدينة اللاذقية - عمران هاني; دكاك أمل; صقر فتاة (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يحاول هذا البحث التّعريف بأهم العوامل الاجتماعية، التي تسهم في تدني مستوى التحصيل الدراسي، في الحلقة الأولى من التعليم الأساسي. لقد تم توضيح تلك العوامل من خلال دراسة نظرية وأخرى ميدانية أجريت في مدينة اللاذقية للعام الدراسي (2011 – 2012). وتتضمن الدراسة النظرية شرحاً لمفهوم التنشئة الاجتماعية للطفولة والدور التربوي الذي تشكله الأسرة في حياة الطالب المدرسية، من خلال الظروف المحيطة بها وأساليب التنشئة المتبعة فيها. وأظهر البحث أيضاً أهمية العلاقات الاجتماعية في المدرسة بين المعلم والطالب والعلاقة مع الأصدقاء في المدرسة ومدى تأثر تحصيل التلميذ بهذه العلاقات، بالإضافة إلى العلاقة بين مشاهدة التلفاز وتدني التحصيل. وتتضمن الدراسة الميدانية إجراءات البحث المنهجية، والتحقق من صحة فروض البحث، وقد انتهى البحث إلى نتائج لافته مفادها أن أهم العوامل الاجتماعية لتدني التحصيل الدراسي هي: (المستوى الاجتماعي المنخفض للأسرة - تفكك الأسرة - أساليب التنشئة الخاطئة - الدور السلبي للتلفاز - العلاقة غير السوية مع الأصدقاء -شخصية المعلم السلبية وانعكاسها في تدني مستوى التحصيل الدراسي. The research tries to define the most important social factors which contribute to the decline of educational achievement in the schools of the first phase of the basic education stage. These factors have been clarified through a theoretical study and a field study that was conducted in Lattakia city in the academic year (2011-2012). The theoretical study includes an explanation of the concept of social upbringing of the children, and the educational role that the family plays in the student’s life via the surrounding environment, and the methods of upbringing. The research also shows the importance of social relations at school between the teacher and students, the relation among friends at school in general and the influence of these relations on the students’ achievement. It yielded many results as to the social factors which contribute to the decline of educational achievement, the most prominent of which are: the low social level of the family; separation within the family; incorrect methods of upbringing; the negative effect of the television; abnormal relations with the friends; the passive character of some teachers.